2018
DOI: 10.3899/jrheum.180028
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective Tapering Algorithm in Patients with Rheumatoid Arthritis: Combination of Multibiomarker Disease Activity Score and Autoantibody Status

Abstract: Objective.To analyze the effect of a risk-stratified disease-modifying antirheumatic drug (DMARD)–tapering algorithm based on multibiomarker disease activity (MBDA) score and anticitrullinated protein antibodies (ACPA) on direct treatment costs for patients with rheumatoid arthritis (RA) in sustained remission.Methods.The study was a posthoc retrospective analysis of direct treatment costs for 146 patients with RA in sustained remission tapering and stopping DMARD treatment, in the prospective randomized RETRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…An article in this issue of The Journal by Hagen, et al, addresses the cost-effectiveness of being able to discontinue DMARD, particularly biological DMARD 14 . If a patient is in medication-free remission with complete control of their RA, their cost of treatment will be dramatically lower than that of a patient who does require medication to control their disease.…”
mentioning
confidence: 99%
“…An article in this issue of The Journal by Hagen, et al, addresses the cost-effectiveness of being able to discontinue DMARD, particularly biological DMARD 14 . If a patient is in medication-free remission with complete control of their RA, their cost of treatment will be dramatically lower than that of a patient who does require medication to control their disease.…”
mentioning
confidence: 99%
“…It has been suggested that the presence of multiple autoantibodies at baseline may reflect a more active autoimmune response which is more susceptible to suppression by MTX in the initial stages, but not in later stages [32]. Indeed, ACPA positivity has been associated with lower rates of drug-free remission in RA in several large studies [33][34][35][36], potentially indicating the persistence of a population of ACPA IgG-producing autoreactive B-cells that is resistant to therapy and accounts for the inability to achieve drug-free remission in RA in the long run [32]. Given that ACPA and RF seropositivity can be helpful in informing response to treatment with other antirheumatic medications in RA (e.g., abatacept and rituximab), confirming the value of differential prediction of early response to MTX treatment in RA by serostatus in future studies may help to further refine the approach to the management of early RA [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…After a follow-up period of 12 months, about 2/3 of patients remained in remission whereas 1/3 experienced a disease flare. The rate of flares was low in the continuation arm (16%) and significantly higher in the tapering (38.9%) and stopping arms (52%)(101).…”
mentioning
confidence: 84%
“…With respect to serum biomarkers, the best-studied predictor of relapse is ACPA positivity. In the BEST study, as well as in the RETRO and HIT-HARD studies, ACPA positivity was associated with higher relapse risk and failure of b-DMARDs discontinuation (73,101,105). In a very recent study, serum calprotectin resulted as an independent predictor of relapse in a cohort of patients with RA and psoriatic arthritis (106).…”
Section: Predictors For Disease Relapse After Dmards Taperingmentioning
confidence: 97%